2014
DOI: 10.1371/journal.pone.0100196
|View full text |Cite
|
Sign up to set email alerts
|

Morphine Enhances HIV-1SF162-Mediated Neuron Death and Delays Recovery of Injured Neurites

Abstract: HIV-1 enters the CNS soon after initial systemic infection; within the CNS parenchyma infected and/or activated perivascular macrophages, microglia and astrocytes release viral and cellular toxins that drive secondary toxicity in neurons and other cell types. Our previous work has largely modeled HIV-neuropathology using the individual viral proteins Tat or gp120, with murine striatal neurons as targets. To model disease processes more closely, the current study uses supernatant from HIV-1-infected cells. Supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 82 publications
(122 reference statements)
1
20
0
Order By: Relevance
“…We also tested effects of HIV + sup and morphine on cortical and hippocampal neurons. Neurons were cultured as previously described (Masvekar et al, 2014; Podhaizer et al, 2012; Zou et al, 2011a; Zou et al, 2011b). In brief, striata or cortices from E15–E16 or hippocampi from P0–P1 ICR (CD-1) mice (Charles River Laboratories International, Inc., Wilmington, MA) were dissected, minced and incubated with trypsin (2.5 mg/ml; Sigma-Aldrich, St. Louis, MO) and deoxyribonuclease (DNase; 0.015 mg/ml; Sigma-Aldrich) in neurobasal medium (Gibco, Grand Island, NY) for 30 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…We also tested effects of HIV + sup and morphine on cortical and hippocampal neurons. Neurons were cultured as previously described (Masvekar et al, 2014; Podhaizer et al, 2012; Zou et al, 2011a; Zou et al, 2011b). In brief, striata or cortices from E15–E16 or hippocampi from P0–P1 ICR (CD-1) mice (Charles River Laboratories International, Inc., Wilmington, MA) were dissected, minced and incubated with trypsin (2.5 mg/ml; Sigma-Aldrich, St. Louis, MO) and deoxyribonuclease (DNase; 0.015 mg/ml; Sigma-Aldrich) in neurobasal medium (Gibco, Grand Island, NY) for 30 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous studies showed that supernatants from HIV-infected cells induce neurotoxic effects in a concentration-dependent manner over a range of p24 levels (10–500 pg/ml), but the interactions with morphine were significant only at lower HIV-exposure levels (p24 = 10 and 25 pg/ml) (Masvekar et al, 2014). Thus, current studies used an HIV + sup exposure level of p24 = 25 pg/ml.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations